2019
DOI: 10.1080/13880209.2019.1676266
|View full text |Cite
|
Sign up to set email alerts
|

Sauromatum guttatum extract promotes wound healing and tissue regeneration in a burn mouse model via up-regulation of growth factors

Abstract: Contexts: Sauromatum guttatum (Wall.) Schott (Araceae) has been traditionally used for the treatment of wounds.Objectives: This study evaluates the healing and tissue regeneration potential of S. guttatum extract in burn wounds.Materials and methods: S. guttatum extract was analysed using various chemical tests, thin layer chromatography (TLC) and high-performance liquid chromatography (HPLC). Moreover, the extract was tested against burn associated bacteria and minimum inhibitory concentration (MIC) was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Celosia argentea extract ointment (10%) for example, induced early wound closure in the rats when compared with control group after 21 days (P < 0.001) (Guo et al, 2016). Sauromatum guttatum extract (2% w/w), in another study, decreased by 72% the rate of wound area with topical ointment prepared in petroleum jelly (Said et al, 2019).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Celosia argentea extract ointment (10%) for example, induced early wound closure in the rats when compared with control group after 21 days (P < 0.001) (Guo et al, 2016). Sauromatum guttatum extract (2% w/w), in another study, decreased by 72% the rate of wound area with topical ointment prepared in petroleum jelly (Said et al, 2019).…”
Section: Discussionmentioning
confidence: 88%
“…Wounds can be defined as injuries occurring in living tissues that are usually caused by a cut, blow, burn or other impact, typically one in which the skin is cut or broken. Preheated materials applied directly on the skin are usually used to induce this type of wound (Cai et al, 2014;Said et al, 2019;Seyhan, 2020). The restoration of the disturbed functional status of the skin and disrupted anatomical continuity requires proper wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biological process of burn wound healing is complex and is influenced by several factors, such as the health and nutritional conditions of the patient and the degree and thickness of the burn on the skin 42,43. Treatment of wound ulcers with Lobelia alsinoides Lam ointment treated groups increased the rate of the healing process and enhanced the collagen deposition compared to the control ointment treatment groups, suggesting a better repair process 44. The macroscopic examination showed that Lobelia alsinoides Lam ointment could also accelerate the healing process of the burn ulcers 45.…”
mentioning
confidence: 99%